Jeremiah Invented: Constructions and Deconstructions of Jeremiah - Holt, Else K. (The Library of Hebrew Bible / Old Testament Studies, 2015)
In the first half of the 20th century there was immense scholarly interest in the biography of the prophet Jeremiah as the background for understanding the development of the book of Jeremiah. Around the turn of the century this interest disappeared, but it has now resurfaced in a transformed configuration as work seeking to analyze the creation of the literary persona, Jeremiah the prophet. This volume examines the construction of Jeremiah in the prophetic book and its afterlife, presenting a wide range of scholarly approaches spanning the understanding of Jeremiah from Old Testament times v